The effects of TV unhealthy food brand placement on children. Its separate and joint effect with advertising. (1st August 2015) - Uribe, Rodrigo; Fuentes-García, Alejandra
Highlights: Placement increases brand recall and disposition toward product category and brand. Placement plus advertising increase the effect on brand awareness and behavioral disposition. Age moderates the effects of the separate and joint use of placement on children. Abstract: This paper examines the effect of unhealthy food brand placement on children across different age groups (9, 12 and 15 year-old children). Results show that both brand awareness, and the behavioral disposition (toward junk food and McDonald's) increased when children were exposed to this marketing technique (in comparison with the control group). In the case of age, older groups (12–15) performed better in brand awareness, but scored lower in behavioral disposition than the 9-year-old group. Moreover, the joint use of advertising and placement (synergy) increased the effect of these communication tactics on children. Results are discussed in terms of previous results of the studies providing evidence of the influence of promotional tools of junk food on children.